X-ray diffraction method for determination of interplanar spacing and temperature distribution in crystals under an external temperature gradient - Kocharian V. R. Vagan Rashidovich; Gogolev A. S. Aleksey Sergeevich; Movsisyan A. E. Artur Egisheevich; Beybutyan A. H.; Khlopuzyan S. G.; Aloyan L. Lusine (2015, 2015)
Title screen